PENINGKATAN HASIL BELAJAR IPS PADA MATERI GEJALA ALAM NEGARA INDONESIA DAN NEGARA TETANGGA DENGAN PENGGUNAKAN TEKNIK THE POWER OF TWO SISWA KELAS VI B SDN 37 PEKANBARU - Gimin Gimin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is based on the low social science learning outcomes on the basic competencies "Symptoms of the Nature of Indonesia and Neighboring Countries" VIB Class students of  SDN 37 Pekanbaru. Problem solving in this study uses the power of two techniques. This study aims to improve social studies learning outcomes of students in VIB class SDN 37 Pekanbaru. The results of this study show, seen from the pre-cycle average value of students amounted to 45.48 (very poor) with students completeness only 7 people or 22.58%, after improvement in the first cycle, the average student increased to 68.70 (moderate) with student completeness as many as 22 students or 70.96%, while in the second cycle, again increased to 82.58 (very good) with the completeness of students as many as 29 students or 93.54%. Based on the results of the study it can be concluded that the technique of the power of two can improve the low social studies learning outcomes on the material Symptoms of the Nature of the Country of Indonesia and the Neighbors of VIB students in the SDN 37 Pekanbaru.